2011
DOI: 10.1155/2011/436704
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of a Thermophysical Property of Molten Semiconductors

Abstract: This paper deals with theoretical approach to surface tension of molten silicon and germanium, and contributes to this field, which is very important. A theoretical calculation for determining the surface tension of high-temperature semiconductor melts, such as molten silicon and germanium, in the temperature range 1687-1825 K and 1211-1400 K, respectively, is described. The calculated temperature-dependence surface tension data for both Si and Ge are expressed as γ = 876 − 0.32 (T − T m ) and γ = 571 − 0.074 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Yet, it is important to emphasize at this point that for the specific case of Ge, all studies reported in literature consistently yield a negative sign of d𝛾/dT for the range from the melting temperature T m up to (T m + 250 K). [34,35] This striking disagreement leaves us with three possible explanations: First, that the gradient becomes positive at much higher temperatures. While this possibility cannot be excluded, it is a mere speculation and brings up the question, why such unusual behavior of the gradient has not been observed before.…”
Section: Formation Mechanisms: Contribution From Marangoni Convectionmentioning
confidence: 99%
“…Yet, it is important to emphasize at this point that for the specific case of Ge, all studies reported in literature consistently yield a negative sign of d𝛾/dT for the range from the melting temperature T m up to (T m + 250 K). [34,35] This striking disagreement leaves us with three possible explanations: First, that the gradient becomes positive at much higher temperatures. While this possibility cannot be excluded, it is a mere speculation and brings up the question, why such unusual behavior of the gradient has not been observed before.…”
Section: Formation Mechanisms: Contribution From Marangoni Convectionmentioning
confidence: 99%